Lethal and sublethal effects of insecticides used in cotton crop on the mealybug endoparasitoid Aenasius arizonensis. Issue 1 (2nd January 2020) - Karmakar, Prasun; Shera, P.S.
Abstract: Lethal effects of eight insecticides at field dosages recommended in cotton crop were assessed against Aenasius arizonensis (Girault) (Hymenoptera: Encyrtidae), a key endoparasitoid of the mealybug Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae). Based on adult mortality, spiromesifen, buprofezin and flonicamid were categorized as slightly harmful, whereas, profenophos, sulfoxaflor, diafenthiuron, imidacloprid and thiodicarb were categorized as harmful insecticides according to the classification proposed by International Organization for Biological Control (IOBC). On exposure of mummies to insecticides, spiromesifen, buprofezin and flonicamid were categorized as harmless, whereas, profenophos and sulfoxaflor were highly toxic on the basis of reduction in adult emergence. Afterward, adults of A. arizonensis emerged from mummies exposed to four insecticides (spiromesifen, flonicamid, buprofezin and imidacloprid) were evaluated for sublethal effects in the subsequent generation. Spiromesifen and flonicamid caused the lowest reduction in parasitism rate of the parasitoid (harmless), while imidacloprid and buprofezin the most (slightly harmful). Imidacloprid significantly prolonged the development time and also reduced the longevity of A. arizonensis . However, buprofezin had no effect on development time of the parasitoid. All these four insecticides did not have any negative effect on the sex-ratio of A. arizonensis . Buprofezin, spiromesifen and flonicamid could facilitate biologically-based integrated pest management programs in cotton agroecosystem